Characterization of jute fibre-epoxy reinforced composites. (2021) - Gopinath, P.; Murugesan, P.; Manjula Devi, R; Venkatesan, M.; Sudha, K.; Kannan, J.C.; Keerthika, P.
Abstract: By incorporating fibre, the comparatively low strength and stiffness qualities of most composites can be improved. The processing and characterization of organic jute fibre reinforced composites has been examined in the current investigation. Jute fibre was used as filler and epoxy resin as matrix in this work. Using hand debilitate method, the composites samples were prepared in the Hi-tech Rudolf laboratory with a suitable fabricating method and quality control. With various proportions of fibres and matrix ratios, the prepared composites are randomly orientated. The SEM, FTIR, impact and hardness tests were employed. From the test results, the increase in the composite's jute fibre volume fraction caused the impact energy and hardness strength of the composite to increase. In addition Taguchi analysis is performed for optimization of single response problem.